The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12947-016-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of longitudinal strain in layer-specific myocardium during normal pregnancy in China

Abstract: BackgroundThe myocardial wall of the left ventricle is a complex, multilayered structure and is not homogenous. The aim of this study was to determine longitudinal strain (LS) in the three myocardial layers in normal pregnant women according to gestation proceedings.MethodsThe advanced two-dimensional speckle tracking echocardiography (2D STE) was performed on 62 women during each pregnancy trimester and 6 to 9 weeks after delivery, while 30 age-matched, healthy, nonpregnant women served as controls. LS on end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
5
3
0
Order By: Relevance
“…In this study, we found the ventricular global longitudinal strain decreased significantly in the third trimester of pregnancy. This is similar to the previous studies, [13,14]. Although there are no significant changes in global radial and circular strain parameters during pregnancy, left ventricular rotation and twist values increase significantly in the 3rd trimester [13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found the ventricular global longitudinal strain decreased significantly in the third trimester of pregnancy. This is similar to the previous studies, [13,14]. Although there are no significant changes in global radial and circular strain parameters during pregnancy, left ventricular rotation and twist values increase significantly in the 3rd trimester [13,14].…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to the previous studies, [13,14]. Although there are no significant changes in global radial and circular strain parameters during pregnancy, left ventricular rotation and twist values increase significantly in the 3rd trimester [13,14]. In the evaluation made in terms of the rotation rate, reversed rotation rate increased in the early period of pregnancy and decreased to control values in the last trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…First, normative values for strain during pregnancy have not been established, although some studies suggest that strain worsens during the third trimester. 12,13 Average strain rates in our control cohort are similar to those reported in the literature. We aimed to account for pregnancy-related changes in strain by matching on gestational age and other clinical factors, although it was not possible to match on all relevant factors.…”
Section: Discussionsupporting
confidence: 86%
“…[37,38] Apparently, evaluation of myocardial deformation just across the ventricular wall thickness is not able to provide comprehensive information on the cardiac function. [39]…”
Section: Discussionmentioning
confidence: 99%